2008
DOI: 10.1128/jvi.00894-08
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cellular Protein, VPEF, Facilitates Vaccinia Virus Penetration into HeLa Cells through Fluid Phase Endocytosis

Abstract: Vaccinia virus is a large DNA virus that infects many cell cultures in vitro and animal species in vivo.Although it has been used widely as a vaccine, its cell entry pathway remains unclear. In this study, we showed that vaccinia virus intracellular mature virions bound to the filopodia of HeLa cells and moved toward the cell body and entered the cell through an endocytic route that required a dynamin-mediated pathway but not a clathrin-or caveola-mediated pathway. Moreover, virus penetration required a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
118
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 63 publications
(66 reference statements)
6
118
0
Order By: Relevance
“…We and others have previously shown that the vacuoles containing MVs also contain fluid markers such as dextran, and that they are devoid of transferrin, a cellular cargo molecule present in early and recycling endosomes 34, 35, 37, 38. This is consistent with reports indicating that classical endosomes and macropinosomes give rise to distinct transport vesicle populations 28.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We and others have previously shown that the vacuoles containing MVs also contain fluid markers such as dextran, and that they are devoid of transferrin, a cellular cargo molecule present in early and recycling endosomes 34, 35, 37, 38. This is consistent with reports indicating that classical endosomes and macropinosomes give rise to distinct transport vesicle populations 28.…”
Section: Discussionsupporting
confidence: 91%
“…VACV MVs and EVs initiate entry into host cells by triggering their own macropinocytic uptake 34, 35, 37, 38. About 30 min later, the viral core is delivered into the cytosol after fusion of the viral envelope with the limiting membrane of endocytic vacuoles 39, 46.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The viral L1 protein also mediates nonglycosaminoglycan binding to cells (11). Subsequently, the MV particles cluster at membrane lipid rafts (12), interact with integrin (13) and CD98 (14), and then undergo endocytosis (15)(16)(17). After uptake into cellular vesicles, the acidic environment triggers membrane fusion mediated by the viral entry fusion complex (18).…”
mentioning
confidence: 99%